Functional Outcome and Complications Following PHILOS Plate Fixation inProximal Humeral Fractures - Hussain, Shafqat; Amin, Muhammad Suhail; Hussain, Mehmood; Munir, Ali Arslan; Jabeen, Sundus; Iqbal, Muhammad Noman (Pakistan Armed Forces Medical Journal, 2024)
Objective: The purpose of this study is to assess the functional outcome following plate fixation with the Proximal Humeral Internal Locking System and to study complications associated with it. Study design: Prospective longitudinal study. Place and duration of study: Department of Orthopedic Surgery, Combined Military Hospital, Rawalpindi Pakistan, for 14 months from 01 Sep 2021 – 31 Oct 2022. Methodology: A total of 75 patients participated in this study. Patients included in the study were aged 18 years or above with displaced proximal Humeral fractures. Patients were selected from in-patient department. They were explained the purpose of the study and those who consented to participate in the study were enrolled through a written consent form. Proximal Humeral Interlocking system was applied under general anesthesia. Follow up at 01 months, 03 months and 06 months was carried out for functional outcome & complications if any. Results: A total of 75 patients were registered in this study. Average age of cohort was 42.05±15.83 years with 46 males and 29 females. At 06 months the mean Constant score of the cohort was 58.96±6.44 and mean ASES score was 60.15±8.08. Most common complication seen was superficial wound site infection with a frequency of 6(8%) that was resolved with dressing. Conclusion: Functional outcome of Proximal Humeral Fractures managed with Interlocking system is very effective, though it declines with age. Early mobilization of shoulder joint is achievable without compromising union of fracture segments.